(untitled) - Slatter, Stuart St. P. (London, 1977)
This book examines the competitive structure and marketing behaviour of the pharmaceutical industry in the United Kingdom.
Keywords: Pharmaceutical industry,Drugs,Công nghiệp dược phẩm,Thuốc; Marketing,Tiếp thị; Great Britain,Nước Anh